Response of a Pioneering Species (Leptospermum scoparium J.R.Forst. & G.Forst.) to Heterogeneity in a Low-Fertility Soil - Gutiérrez-Ginés, Maria Jesus; Madejón, Engracia; Lehto, Niklas J.; McLenaghen, Roger D.; Horswell, Jacqui; Dickinson, Nicholas; Robinson, Brett H. (Frontiers in Plant Science, 2019)
Root foraging may increase plant nutrient acquisition at the cost of reducing the total volume of soil explored, thereby reducing the chance of the roots encountering additional patches. Patches in soil seldom contain just one nutrient: the patch may also have distinct textural, hydrological, and toxicological characteristics. We sought to determine the characteristics of root foraging by a pioneering species, Leptospermum scoparium, using pot trials and rhizobox experiments with patches of biosolids. The growth of L. scoparium was increased by <50 t/ha equiv. of biosolids but higher doses were inhibitory. Roots foraged patches of biosolids in a low-fertility soil. There was no evidence of chemotaxis, rather, the roots proliferated towards the patch of biosolids, following chemical gradients of nitrate. While the biosolids also contained high concentrations of other nutrients (P, K, S), only significant chemical gradients of nitrate were found. Once the roots encountered a patch of biosolids, the growth of the plant increased to a level similar to plants growing in soil homogeneously mixed with biosolids or surface-applied biosolids. Our results indicate that roots forage nitrate, which is mobile in soil, and that gradients of nitrate may lead to patches containing other less mobile nutrients, such as phosphate or potassium.